2018
DOI: 10.3389/fimmu.2018.00474
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Reconfiguration of Natural Killer Cells in HIV-1 Infection

Abstract: Human cytomegalovirus (HCMV) co-infection is highly prevalent within HIV-1 cohorts and is an important cofactor in driving ongoing immune activation, even during effective antiretroviral treatment. HCMV infection has recently been associated with expansion of adaptive-like natural killer (NK) cells, which harbor epigenetic alterations that impact on their cellular function and phenotype. The influence of HCMV co-infection on the considerable heterogeneity among NK cells and their functional responses to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 51 publications
7
67
0
Order By: Relevance
“…We also show that in our cohort of HIV-infected women, TIGIT + NK cells exhibit a more adaptive/mature phenotype (CD57 hi , NKG2C hi , LILRB1 hi , FcRγ lo , Syk lo ) and adaptive NK cells demonstrated higher TIGIT expression in unsupervised clustering via UMAP. This is consistent with the notion that NK cells undergo an adaptive reconfiguration during HIV infection [65]. Notably, Sarhan et al demonstrated that TIGIT was expressed at lower levels in adaptive NK cells from healthy donors [70].…”
Section: Nk Cells Undergo Significant Changes During Chronic Hiv Infesupporting
confidence: 86%
See 1 more Smart Citation
“…We also show that in our cohort of HIV-infected women, TIGIT + NK cells exhibit a more adaptive/mature phenotype (CD57 hi , NKG2C hi , LILRB1 hi , FcRγ lo , Syk lo ) and adaptive NK cells demonstrated higher TIGIT expression in unsupervised clustering via UMAP. This is consistent with the notion that NK cells undergo an adaptive reconfiguration during HIV infection [65]. Notably, Sarhan et al demonstrated that TIGIT was expressed at lower levels in adaptive NK cells from healthy donors [70].…”
Section: Nk Cells Undergo Significant Changes During Chronic Hiv Infesupporting
confidence: 86%
“…TIGIT + NK cells also exhibited increased responses to PMA/ionomycin, cytokine and tumor cells, compared to TIGIT -NK cells (Figures 5d and 5e). [16,64], with expansion of a hypofunctional CD56 -CD16 + NK cell subpopulation [10,11], downregulation of several activating NK cell receptors [12][13][14], and adaptive reconfiguration [65]. Some of these changes are not observed after treatment or in the setting of natural HIV control [66], indicating that diminished NK cell function could contribute to disease pathogenesis.…”
Section: Tigit Expression Is Associated With Increased Nk Cell Responsesmentioning
confidence: 99%
“…PD-1 expression is also increased in HIV infection even with ART treatment, and these cells have limited proliferative capacity and may contribute to NK cell dysfunction (Norris et al, 2012). The increased expression of NKG2C and CD2 may reflect an increase in a subset of NK cells with a more mature, adaptive phenotype that is known to expand during HIV infection, and that persists even during ART treatment (Peppa et al, 2018). Indeed, we observed differential abundance of cluster 3 (Fig 4) between the HIV+ and HIV-groups; this cluster, which had greater abundance in donors of the HIV+ group, expressed high levels of CD2 and low levels of Siglec-7, and expressed both NKG2C and CD57, all known features of this subset.…”
Section: Discussionmentioning
confidence: 99%
“…Natural Killer (NK) cells play a key role in antiviral immunity and a number of studies implicate NK cells as critical contributors to immune control of HIV-1 (Fauci et al, 2005) (Martin et al, 2002) (Martin et al, 2007). It is well documented that persistent HIV-1 infection alters the subset distribution and functional capacity of NK cells (Peppa et al, 2018) (Bradley et al, 2018) (Altfeld et al, 2011). In particular HCMV co-infection, a hallmark of HIV-1 infected cohorts, triggers a dramatic expansion of differentiated NK cells expressing the activating receptor NKG2C, which prototypically characterises adaptive NK cells (Guma et al, 2006) (Mela and Goodier, 2007) (Brunetta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Notably they resemble memory CD8 T cells and are imbued with enhanced capacity for antibody dependent cellular cytotoxicity (ADCC), in particular increased IFN-γ production attributed to epigenetic remodelling of the IFNG locus (Schlums et al, 2015) (Lee et al, 2015). The adaptive reconfiguration of NK cells during HIV-1 infection is further delineated by loss of the transcription factor promyelocytic leukaemia zinc finger protein (PLZF), and downstream signalling molecules such as FcεRI-γ (Peppa et al, 2018), which partly overlap with NKG2C expression. While these attributes are considered important in the functional specialisation of these NK cells, the development of these features under conditions of continuous stimulation/persistent inflammation during HIV-1 infection could lead to the establishment of functionally and metabolically exhausted NK cells akin to exhausted CD8 T cells.…”
Section: Introductionmentioning
confidence: 99%